2010
DOI: 10.1007/s11671-010-9599-9
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and Magnetic Properties of Nearly Monodisperse CoFe2O4 Nanoparticles Through a Simple Hydrothermal Condition

Abstract: Nearly monodisperse cobalt ferrite (CoFe2O4) nanoparticles without any size-selection process have been prepared through an alluring method in an oleylamine/ethanol/water system. Well-defined nanospheres with an average size of 5.5 nm have been synthesized using metal chloride as the law materials and oleic amine as the capping agent, through a general liquid–solid-solution (LSS) process. Magnetic measurement indicates that the particles exhibit a very high coercivity at 10 K and perform superparamagnetism at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(67 citation statements)
references
References 31 publications
(38 reference statements)
1
58
0
2
Order By: Relevance
“…The main problems of these methods are the particle size and shape cannot be control and agglomerated particles are formed. These situations limit their applications (Li, Xu, Han, Qiao, Wang, & Li, 2010). (Pillai & Shah, 1996).…”
Section: Figure 15mentioning
confidence: 99%
“…The main problems of these methods are the particle size and shape cannot be control and agglomerated particles are formed. These situations limit their applications (Li, Xu, Han, Qiao, Wang, & Li, 2010). (Pillai & Shah, 1996).…”
Section: Figure 15mentioning
confidence: 99%
“…In our present study we are able to synthesized particles having diameter around 11 nm to 14 nm with high crystallinity keeping sintering temperature 550 0 C for 30 minutes which are quite low and quick respectively.Almost similar kind of sintering temperature resulted in higher crystallite sizes of cobalt ferrite prepared by citrate precursor method[36]. In addition, similar value of saturation magnetization M s have been reported for CoFe 2 O 4 nanoparticles prepared under a simple hydrothermal condition[37], single domain CoFe 2 O 4 nanoparticles synthesized by coprecipitation method[38].Thus it is observed that doping of Ni and Mn in nanocrystalline cobalt ferrite can enhance the magnetic properties by changing the cation distribution between the two sublattices. Calculated magnetic moment using our proposition of cation distribution perfectly matches with experimental observation which also corroborate with Rietveld analysis.…”
mentioning
confidence: 52%
“…The single-phase CoFe 2 O 4 synthesized by conventional ignition from citric acid exhibits lower magnetization of 53 emu/g than that of the bulk CoFe 2 O 4 (80 emu/g [7]), due to surface spin disorder or spin canting effects. On the surface, the spin orientation cannot be the same as that of the magnetic core and hence the saturation magnetization is reduced [31]. Furthermore, the high coercivity (Hc = 1500 Oe) of the as-combusted CCA sample can be attributed to the small particle size.…”
Section: Methodsmentioning
confidence: 99%